2009
DOI: 10.3201/eid1508.090264
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Death after SevereStreptococcus pyogenesInfection

Abstract: An evaluation of the relative importance of host and pathogen factors on the survival rates of patients with invasive Streptococcus pyogenes infection found a number of clinical and demographic factors to be associated with risk for death. Some evidence suggested a seasonal pattern to patient survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 14 publications
3
45
0
4
Order By: Relevance
“…Almost half of all fatalities occurred within the first 48 hours of admission. These results are comparable to that of another study [24], emphasising the importance of early recognition and treatment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Almost half of all fatalities occurred within the first 48 hours of admission. These results are comparable to that of another study [24], emphasising the importance of early recognition and treatment.…”
Section: Discussionsupporting
confidence: 88%
“…In support of this theory, we observed an association between severity of IGASI and seasonality, with a higher proportion of severe cases in January to April compared with the average in June to September. Another study from the United Kingdom [24] had also demonstrated a seasonal difference in case severity, with more severe infections diagnosed in January.…”
Section: Discussionmentioning
confidence: 96%
“…4,6,11,13,35 Also, in this study the time elapsed between the onset of symptoms and the introduction of treatment with adequate antibiotics was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence is 3-fold higher among persons >70 years of age, particularly among the very elderly (1,2,4). Older persons have also been shown to have higher case-fatality rates, including in studies considering particular clinical syndromes, suggesting that age is a risk for death independent of the clinical form of iGAS (1,5,6). Population-based study data estimate incidence among long-term care facility (LTCF) residents as 3.4-fold (7), 6.0-fold (8), and 7.8-fold (9) higher than that among elderly persons living outside institutional settings.…”
mentioning
confidence: 98%